Relationships between physical activity, physical fitness and mortality among the elderly: Fibra Study - Maria Nevoni Ferreira de Araujo, Célia; Martins Pinto, Juliana; Liberalesso Neri, Anita; José D’Elboux, Maria (O Mundo da Saúde, 2020)
Being physically active and maintaining great physical fitness protect older adults against early death. However, is not clear through which mechanisms such relationships occur or whether physical fitness is required to prevent mortality in this population. The objective was to investigate relationships between physical activity, physical fitness and occurrence of death among the elderly residing in a community and explore the mediating effects. A cross-sectional study from FIBRA Study database, collected in Campinas city, in Sao Paulo state, Brazil between 2008 and 2009 was performed. The occurrence of death was verified in August 2017 in the Mortality Information System (MIS). Physical activity was measured through self-reporting while physical fitness was measured through physical performance tests with 800 participants aged 65 years or older. A model was drawn to test relationships and mediating effects between global, leisurely, domestic physical activities, physical fitness, and mortality, controlled by sex and age. The results demonstrated three main findings: 1) the direct effect of global physical activity on death and its indirect effect mediated by slowness; 2) the direct effect of domestic activity on death and its mediated effect through weakness; and 3) the direct effect of slowness on death. Physically inactive, weak and slow elderly have a greater probability of death. Moreover, the benefits of physical activity are probably beyond physical fitness.